Design Model for Development of Student Interests in Investing in the Investment Gallery of the University of Muhammadiyah Makassar - Arniati Arniati; Naidah Naidah; Andi Arifwangsa Adiningrat; Muh. Haikal Fikri; Iin Febriyanti; Ade Wahyu (Universitas Muhammadiyah Enrekang, 2024)
The aim of the study was to determine the level of effectiveness of the design model for developing student interest in investing in the Muhammadiyah University Makassar Investment Gallery. The specific target to be achieved in this research is the design of a model for developing interest in investing when students are still in the study environment to be effective and provide benefits, for example saving to guarantee the future and saving to study and make a profit. This study uses applied qualitative methods. Data collection techniques are library research, interviews and observation. As for the research instruments for the initial study, validation and try out questionnaires were used for students and the community. Meanwhile for the design of the model an achievement test was used to develop interest in investing for students. With the development model design, the level of effectiveness is high for students who are interested in investing independently and influence their friends both directly and indirectly. Students are also agents of change in society, from a consumptive society to a productive society by investing.